(untitled) (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. Fitness is an ability and ability This research aims to determine the relationship between physical fitness and cognitive ability of students in grade VIII A SMP Negeri 8 Cirebon City. The background of the research is based on the low level of student fitness and the absence of similar research in the school. Materials and methods. The research method used is quantitative descriptive with a survey approach and instruments in the form of the Indonesian Physical Fitness Test (TKJI) and PJOK subject report card scores as indicators of cognitive ability. The research sample amounted to 27 students who were selected through purposive sampling techniques. Results. The results showed that most students were in the "moderate" physical fitness category and the PJOK report card scores were all in the "good" category. The normality test showed normally distributed data, but the product moment correlation test yielded a significance value of 0.830 (> 0.05), meaning there was no significant relationship between physical fitness and students’ cognitive abilities. Conclusion. Thus, it can be concluded that physical fitness is not a factor that is directly related to students’ cognitive abilities in the context of this study.